PENGARUH PEER COACHING TERHADAP PRAKTEK PEMBELAJARAN IPA GURU SD (Studi Kuasi Eksperimen SD di Pekanbaru) - M. Jaya Adi Putra (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2013)
This study investigates one of the alternatives increase the ability of teachers in theprocess of learning science in the classroom using peer coaching. This research was conductedin Pekanbaru with a total sample of eight teachers were divided into experimental and control.The result in this study impact on the success of teacher inquiry to bring all aspects of learning.